The Implementation of Digital Technology to Support Self-Care among Heart Failure Patients: A Literature Review - Efadatus Zakiyah; Riri Maria; Dikha Ayu Kurnia (Indonesian Journal of Global Health Research, 2026)
Heart failure has high morbidity and mortality rates, with a prevalence ranging from 1–2% in the adult population, increasing to more than 10% in people over 70 years of age. Self-care abilities are very low. Technologies such as mHealth, telemonitoring, and SMS can support the education and monitoring of heart failure patients. Objective to evaluate the impact of digital self-care education interventions on improving the behavior and quality of life of heart failure patients. A systematic literature review was conducted using the PRISMA 2020 guidelines, searching databases including PubMed, ScienceDirect, Wiley Online Library, and Clinical Key for Nursing from 2020 to 2025. 10 articles meeting the criteria were identified and analyzed using the JBI tool and 10 article in review. Digital interventions such as mHealth applications, Bluetooth, and educational SMS messages can improve self-care maintenance, symptom recognition, adherence, and quality of life in patients (p < 0.05–0.001). Like medication reminders, symptom alarms can improve and strengthen self-care. However, changes in patient behavior have not fully affected key indicators, such as NT-proBNP, for short-term hospitalization. Digital self-care can improve self-care behaviors among nurses in educating heart failure patients and has the potential to increase independence and quality of life. Long-term research is needed to examine the effect on symptom severity in heart failure patients.